"They're training us to be helpless:" Medical student socialization around social determinants of health - Hannah Connolly (Elsevier, 2023)
Social factors are the primary drivers of health inequity in the United States. Yet, medical trainees remain underprepared to address the social determinants of health in practice, despite curricular innovations. Therefore, there is a critical need to explore how social determinants of health curricula is taken up by medical students. This study, which draws upon ethnographic fieldwork and in-depth interviews at a medical school in the United States, explores how medical students understand their role in addressing social determinants of health. I find that epistemic invulnerability, defined as the closure to affect or to be affected in relation to others, generates feelings of helplessness, closure to alternate possibilities, and rigid professional boundaries that prevent medical students from incorporating the responsibility to act on the social determinants into their clinical purview. These findings provide novel epistemological context to better align health equity curricula in medical education with the aim to train physicians that both understand and address the social determinants of health.